DAMPAK MODERNISASI TERHADAP PERGESERAN NILAI PERSATUAN (STUDI KASUS DI DUSUN BEBER) - Nur Husna Wahida; Rahmatun Husnul Hikmah Aulia; Siti Nuraini; Shady Kurnia Pratama; Alfin Wahyu Saputra; Vita Andriani; Moh. Zubair (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
ABSTRACT Along with the development of modernization, many challenges are faced in implementing the values of Pancasila, more specifically the value of unity. The aim of this research was to examine the impact of modernization on the shift in the value of unity in social life in Beber Hamlet. The method used in this research is a qualitative approach, with a case study type. Data collection techniques were used in three ways, namely observation, interviews and documentation. The results of research conducted by the author show that modernization has had many negative impacts on the application of the value of unity, including the waning of the spirit of mutual cooperation and a shift in tradition.